INTEGRATING SUSTAINABLE FARMING PRACTICES INTO HIGH SCHOOL CURRICULA: A CASE STUDY FROM RURAL BRAZIL - Azimova Zilola (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
This paper explores the integration of sustainable farming practices into high school curricula through a case study from rural Brazil. It examines how education can promote environmental awareness, strengthen rural communities, and reshape young people’s perceptions of agriculture. The study discusses the implementation of a school-based sustainable agriculture program in Bahia, Brazil, highlighting its structure, outcomes, and challenges. The findings show that students gained environmental literacy and practical skills, while community engagement improved through school-farmer partnerships. The paper concludes with policy recommendations for scaling such initiatives and promoting sustainability through education.